REDD+and community-controlled forests in low-income countries: Any hope for a linkage? - Bluffstone, R.; Robinson, E.; Guthiga, Paul M. (Elsevier, 2013)
Deforestation and forest degradation are estimated to account for between 12% and 20% of annual greenhouse gas emissions and in the 1990s (largely in the developing world) released about 5.8 Gt per year, which was bigger than all forms of transport combined. The idea behind REDD + is that payments for sequestering carbon can tip the economic balance away from loss of forests and in the process yield climate benefits. Recent analysis has suggested that developing country carbon sequestration can effectively compete with other climate investments as part of a cost effective climate policy. This paper focuses on opportunities and complications associated with bringing community-controlled forests into REDD +. About 25% of developing country forests are community controlled and therefore it is difficult to envision a successful REDD + without coming to terms with community controlled forests. It is widely agreed that REDD + offers opportunities to bring value to developing country forests, but there are also concerns driven by worries related to insecure and poorly defined community forest tenure, informed by often long histories of government unwillingness to meaningfully devolve to communities. Further, communities are complicated systems and it is therefore also of concern that REDD + could destabilize existing well-functioning community forestry systems.